Identification of Potential Core Genes for the Rupture of Intracranial Aneurysms by a Bioinformatics Analysis - Lin, Yuan; Ma, Hai-Ying; Wang, Yi; He, Jiang; Liu, Heng-Jian (Frontiers in Genetics, 2022)
Background: Previous studies, using autopsy and angiography, have shown that 3.6%-6% of the population have intracranial aneurysms, and the rupture of aneurysm can lead to brain dysfunction or even death in patients. Methods: To explore potential preventional target genes for the ruptured of aneurysm, we analyze three gene expression datasets (GSE13353, GSE15629 and GSE54083) derived from the GEO database. We confirm DEGs associated with the unrupture of aneurysms by R package. DAVID version provides functional classification and annotation analyses of associated genes, including GO and KEGG pathway. PPI of these DEGs is analyzed based on the string database and visualized by Cytoscape software. DEGs are verified by qRT-PCR using samples isolated from the patients. Results: 249 overlapping DEGs, including 96 up-regulated genes and 153 down-regulated genes are screened using the Venn diagram webtool. The GO term and KEGG pathways analysis results indicate that these DEGs are mainly enriched in protein phosphorylation, apoptotic process and inflammatory response in the BP term and focal adhesion, thyroid hormone signaling pathway, ErbB signaling pathway, cytokine-cytokine receptor interaction and some disease processes in the KEGG pathways. 6 candidates are confirmed by Cytoscape software and qRT-PCR, including APP, JUN, GSK3B, ErbB2, PPBP and THBS1. Conclusions: Our data and previous studies show that ErbB2 and THBS1 are crucial to prevent aneurysm rupture, while APP, JUN, GSK3B and PPBP performs the opposite role, and further experiments are needed to verify these findings.